Investigating the "circular propensity" of road bio-binders: Effectiveness in hot recycling of reclaimed asphalt and recyclability potential. (10th May 2020) - Ingrassia, Lorenzo Paolo; Lu, Xiaohu; Ferrotti, Gilda; Conti, Carla; Canestrari, Francesco
Abstract: In pavement engineering, the use of bio-binders and reclaimed asphalt (RA) promotes the principles of sustainability and circular economy, without penalizing or even improving the performance. In this regard, this study focuses on the "circular propensity" of bio-binders obtained by partially replacing a conventional bitumen with a bio-oil generated as a residue by the wood and paper industries. Specifically, the objectives are: 1) to assess the effectiveness of bio-binders in the hot recycling of traditional RA and 2) to evaluate, in a long-term perspective, their recyclability potential. For this purpose, two severely aged binders (one "RAP" binder recovered from reclaimed asphalt and one laboratory-produced "Bio-RAP" binder) and two fresh binders (one bio-binder and one bitumen) are blended to reproduce four hot recycled binders. The mechanical behaviour and the aging susceptibility of these blends are compared to those of a control virgin bitumen. The experimental investigation includes conventional tests, rheological testing and modelling (modified CAM model) as well as chemical analysis (Fourier transform infrared spectroscopy). The main results indicate that the hot recycling of reclaimed bio-asphalt (bio-RA) may lead to mixtures less susceptible to cracking as compared to the recycling of conventional RA, as well as the use of bio-binders in the hot recycling of conventional RA may be beneficial in terms of cracking. Even though the blends with the bio-binder are characterized by a lower aging rate, the permanent deformation behaviour of all the recycled blends studied is comparable in unaged and short-term aged conditions, i.e. the circumstances under which rutting is usually a concern. Finally, the recycled blends show significantly lower aging susceptibility than the control bitumen. Overall, these results suggest that the bio-binders studied are effective in the hot recycling of RA and 100% recyclable, and their use in asphalt pavements can lead to significant technical and environmental benefits. Highlights: Recycled blends with bio-binder undergo lower aging than those with bitumen. Blends with bio-binder seem less susceptible to cracking than those with bitumen. High-temperature performance is comparable for all recycled blends. All recycled blends show lower aging susceptibility than the control bitumen. Bio-binders are effective in hot recycling and 100% recyclable.